ANALISIS GERAKAN-GERAKAN KERJA PADA PEMBUATAN RUMAH KUNCI DENGAN MENGGUNAKAN METODE MOTION STUDY - R. Lisye Herlina (ENSAINS JOURNAL, 2019)
Abstract: There is a real challenge to work measurement. The behaviour of human beings, the synergy between people and machines, the dynamics of labor management relation, and the limitation of commodnly used measurement system, interact to create a system which defies success. Motion study is a method to analyse every ineffective and insignificant work motions became the betier ways such as effective and efficient eork motions. These funfamental work motions called by THERBLIG, there are only seventeen work motions of therbligs such as search. Select, Grasp,Transport Empty, Transport Loaded, Hold Release Load, Position, Pre Position, Pre Position Inspection, Assemble, Dissasembly, Use Unavoidable Delays, Avoidble Delay, Plan, Rest to Overcome Fatigue Result of this research presents that the proposed of left and right hand chart has work motions more e Fiective and more efficient than the existing of lefnd right hand chart.Key Words : motion study and THERBLIG